The Relationship of Nitrate, Phosphate, and Silicate Concentrations to The Abundance of Planctonic Diatoms in Carocok Tarusan Waters, Pesisir Selatan District - Yandra, Yoli; Nedi, Syahril; Elizal, Elizal (Journal of Coastal and Ocean Sciences, 2022)
This research was carried out from December 2020 to January 2021 in Carocok Tarusan Waters, Pesisir Selatan Regency, West Sumatra, which aims to analyze the concentration of nitrate, phosphate and silicate, calculate the abundance of planktonic diatoms and analyze the relationship between the content of nitrate, phosphate and silicate to the abundance of planktonic diatoms present. in the waters of Carocok Tarusan, Pesisir Selatan Regency. The research method used in this study is a survey method while the determination of research stations is carried out by purposive sampling. The results showed that the average nitrate concentration was 0.7792– 0.8757 mg/L, the average phosphate concentration was 1.7220– 2.0833 mg/L and the silicate concentration was 0.6287 - 0.6835 mg/L. Planktonic diatoms found in Carocok Tarusan waters contained 13 species from 3 classes, namely Bacillariophyceae, Chaetoceraceae and Coscinodiscophyceae. The results of the calculation of the abundance of planktonic diatoms are 17.82 – 20.72 Ind/L. The test conducted to determine the relationship of nitrate, phosphate and silicate to the abundance of planktonic diatoms was a simple linear regression test. Based on the results of the linear regression test, it is known that the effect of nitrate concentration on the abundance of planktonic diatoms in Carocok Tarusan waters is 00.81%, while the remaining 99.19% is influenced by other factors, for the effect of phosphate concentration on the abundance of planktonic diatoms in Carocok waters. Tarusan is 8.81%, while the remaining 91.19% is influenced by other factors and for the effect of silicate concentration on the abundance of planktonic diatoms in Carocok Tarusan waters as much as 2.97%, while the remaining 97.03% is influenced by other factors